1994
DOI: 10.1111/j.1752-0606.1994.tb00114.x
|View full text |Cite
|
Sign up to set email alerts
|

An Ethnography of Couple and Therapist Experiences in Reflecting Team Practice

Abstract: Couple and therapist perspectives about the use and process of reflecting team practice were analyzed using ethnographic research. A domain analysis was performed on postession interviews from both couples and therapists, and on field notes from each therapist. Seven couples and five therapists were interviewed at least twice over a 4‐month period concerning their reactions to and perceptions of reflecting team practice. Six domains concerning reflecting team practice emerged from the analysis: (a)benefits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
122
4
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(133 citation statements)
references
References 14 publications
6
122
4
1
Order By: Relevance
“…Literature Review A literature review on client perceptions of therapy revealed that studies have focused on: client views of their therapists and the therapeutic relationship (Bachelor, 1988;Golden & Robbins, 1990;Kuehl, Newfield, & Joanning, 1990;Rennie, 1992;Wark, 1994); children's perspectives on their family therapy experiences (Bischoff & McBride, 1996;Stith, Rosen, McCollum, Coleman, & Herman, 1996); comparisons of client and therapist perceptions of therapy (e.g., Bennun, Hahlweg, Schindler, & Langlotz, 1986); comparisons of the effectiveness of different approaches to treatment (Bennun et al, 1986;Parry, Shapiro, & Firth, 1986); clients' views of their treatment at various points during the therapy process (Conran & Love, 1993;Gale, Odell, & Nagireddy, 1995;Lietaer, 1992;Roberts, 1993;Shilts & Knapik-Esposito, 1993); client perspectives on the use of reflecting teams (Sells, Smith, Coe, & Yoshioka, & Robbins 1994;Smith, Sells, & Clevenger, 1994); "significant events" within a given therapy session (e.g., Elliott & Shapiro, 1992), and "effective moments" throughout the course of therapy (Sells, Smith, & Moon, 1996).…”
Section: Downloaded By [Oakland University] At 03:07 25 November 2014mentioning
confidence: 98%
“…Literature Review A literature review on client perceptions of therapy revealed that studies have focused on: client views of their therapists and the therapeutic relationship (Bachelor, 1988;Golden & Robbins, 1990;Kuehl, Newfield, & Joanning, 1990;Rennie, 1992;Wark, 1994); children's perspectives on their family therapy experiences (Bischoff & McBride, 1996;Stith, Rosen, McCollum, Coleman, & Herman, 1996); comparisons of client and therapist perceptions of therapy (e.g., Bennun, Hahlweg, Schindler, & Langlotz, 1986); comparisons of the effectiveness of different approaches to treatment (Bennun et al, 1986;Parry, Shapiro, & Firth, 1986); clients' views of their treatment at various points during the therapy process (Conran & Love, 1993;Gale, Odell, & Nagireddy, 1995;Lietaer, 1992;Roberts, 1993;Shilts & Knapik-Esposito, 1993); client perspectives on the use of reflecting teams (Sells, Smith, Coe, & Yoshioka, & Robbins 1994;Smith, Sells, & Clevenger, 1994); "significant events" within a given therapy session (e.g., Elliott & Shapiro, 1992), and "effective moments" throughout the course of therapy (Sells, Smith, & Moon, 1996).…”
Section: Downloaded By [Oakland University] At 03:07 25 November 2014mentioning
confidence: 98%
“…The ethnographer's biases a re therefo re less important than a Jack of awareness of how those biases might dictate questions and category construction. To illustrate how the issue of bias might be handled, the instructo r should show students several ethnogra phies that re port Downloaded by [University of Alberta] at 18:19 12 December 2014 potential researcher bias before presenting results ( cf., Elks & Kirkhart, 1993;Hoshmand, 1989;Moon et al, 1990;Sells et al, 1994).…”
Section: Module 2: Researcher Characteristics Sampling and Data Colmentioning
confidence: 96%
“…Similarly, comments from families seen by 'reflecting teams', where the team members are present in the room rather than behind the mirror, suggest that the visibility of the team reduces feelings of intimidation and increases confidence (Sells et al, 1994). Establishing the identity of all team members with face-to-face introductions may be a way to do this even when the one-way screen is to be used.…”
Section: Fiona Knott and Colin Espiementioning
confidence: 99%